2021
DOI: 10.1016/j.jpain.2021.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Parallel ascending spinal pathways for affective touch and pain

Abstract: The anterolateral pathway consists of ascending spinal tracts that convey pain, temperature and touch information from the spinal cord to the brain1-4. Projection neurons (PNs) of the anterolateral pathway are attractive therapeutic targets for pain treatment because nociceptive signals emanating from the periphery channel through these spinal PNs en route to the brain.However, the organizational logic of the anterolateral pathway remains elusive. Here, we show that two PN populations that express structurally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 2 publications
2
31
0
Order By: Relevance
“…38,63 Despite this, PVIN photostimulation evoked excitatory input in laminae I-IIo, suggesting most of these cells receive PVIN input through ventrally directed dendrites. 14,25,48,73 Our data that lamina I PNs also receive direct PVIN input suggest a similar arrangement of dendritic extensions into the PVIN plexus. This is supported by our recent characterisation of mouse lamina I PNs, demonstrating dendritic arbours extend more ventral than previously appreciated.…”
Section: Discussionmentioning
confidence: 64%
“…38,63 Despite this, PVIN photostimulation evoked excitatory input in laminae I-IIo, suggesting most of these cells receive PVIN input through ventrally directed dendrites. 14,25,48,73 Our data that lamina I PNs also receive direct PVIN input suggest a similar arrangement of dendritic extensions into the PVIN plexus. This is supported by our recent characterisation of mouse lamina I PNs, demonstrating dendritic arbours extend more ventral than previously appreciated.…”
Section: Discussionmentioning
confidence: 64%
“…In summary, here we have shown that ANs encode high-level behaviors that they convey to distinct integrative sensory and action selection centers in the brain. These findings can accelerate our understanding of how ascending neurons in the mammalian spinal cord influence decision-making in the brain [15, 16, 46, 55–57], and also inspire the development of more effective algorithms for robotic sensory contextualization and action selection [2].…”
Section: Discussionmentioning
confidence: 99%
“…Along with the improvement of devices and methodology, the application of optogenetics at the spinal level helps elucidate the cellular, molecular, and circuit mechanisms of pain transmission and integration with less tissue damage [22,29]. Second-order sensory neurons expressing Tac1 receptor (Tacr1) and GPCR 83 respond to distinct types of stimulation and innervate distinct sets of neurons in the lateral PBN; optogenetic activation of their axon terminals in the PBN induces distinct escape behaviors and autonomic responses [30]. This study reveals two parallel ascending spinal pathways for pain.…”
Section: Spinal Cordmentioning
confidence: 99%